Development and Implementation of Hardware to trigger I/O of a PLC via Wireless Network - Grandinetti, Felipe Naressi (2022)
This work aims to use ESP32 and ESP8266 microprocessors with built-in Wi-Fi modules to activate the digital inputs of a PLC via the Web, in addition to sending the command signal via wireless network to the respective actuators of the system. A local wireless network is created to allow control of inputs via a browser on a cell phone or computers, such as allowing the exchange of information between the controller and its actuators. To test the functionality of the proposed prototype, a three-phase motor was started using the browser of a cell phone connected to the ESP32 Wi-Fi network.